2017
DOI: 10.1002/2017gl073254
|View full text |Cite
|
Sign up to set email alerts
|

Localized water reverberation phases and its impact on backprojection images

Abstract: Coherent radiators imaged by backprojections (BP) are commonly interpreted as part of the rupture process. Nevertheless, artifacts introduced by structure related phases are rarely discriminated from the rupture process. In this study, we use a calibration event to discriminate between rupture and structure effects. We reexamine the waveforms and BP images of the 2012 Mw 7.2 Indian Ocean earthquake and a calibration event (Mw 6.2). The P wave codas of both events present similar shape with characteristic perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
46
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 25 publications
3
46
4
Order By: Relevance
“…However, back‐projection can still suffer from imaging artifacts, depending upon the data coverage and quality, as well as details of the data processing (e.g., Kiser & Ishii, ; Meng et al, ; Xu et al, ). In some cases, depth phases or water reverberations may cause coherent radiation, contaminating the back‐projection images (e.g., Xu et al, ; Yue et al, ). Thus, evaluating the resolution and robustness of back‐projection results is important and can be done using synthetic experiments (e.g., Koper et al, ) or back‐projecting smaller earthquakes near the mainshock rupture to estimate the imaging kernel for a point source (e.g., Wang & Mori, ).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, back‐projection can still suffer from imaging artifacts, depending upon the data coverage and quality, as well as details of the data processing (e.g., Kiser & Ishii, ; Meng et al, ; Xu et al, ). In some cases, depth phases or water reverberations may cause coherent radiation, contaminating the back‐projection images (e.g., Xu et al, ; Yue et al, ). Thus, evaluating the resolution and robustness of back‐projection results is important and can be done using synthetic experiments (e.g., Koper et al, ) or back‐projecting smaller earthquakes near the mainshock rupture to estimate the imaging kernel for a point source (e.g., Wang & Mori, ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Yue et al () examined the anomalous arrivals in the P wave trains of the 2012 M w 7.2 Sumatra earthquake and concluded that they probably originated from mainshock water reverberations rather than from an early aftershock, based on both observational details and a 2‐D synthetic simulation. A key part of their argument involves a comparison between the mainshock and a nearby M 6 earthquake, which they claim contains anomalous late P wave arrivals similar in character to those seen for the mainshock, and yields back‐projection images with energy near the location of the early aftershock(s) imaged by Fan and Shearer () for the mainshock.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations